Efeito do retratamento endodôntico sobre a resistência de união de cimentos resinosos à dentina intrarradicular - Pereira, Kamila de Figueiredo [UNESP] (2015)
The aim of this study was to evaluate the effect of endodontic retreatment on the bond strength and the penetrability of different cementing systems of fiberglass posts to root dentin through the push out bond strength, confocal laser microscopy and scanning electron microscopy. Sixty human teeth with single canals and ovalshaped were used (n=15): ETA - Endodontic treatment and cementation with RelyX ARC; ETU - Endodontic treatment and cementation U200; ERA - Endodontic retreatment and cementation RelyX ARC; ERU - Endodontic retreatment and cementation with U200. The groups with conventional endodontic treatment were filled with AH plus (ETA and ETU) and the groups that suffered endodontic retreatment were filled, primarily, with Endofill and, after, with AH Plus.  The fiber glass posts received as a previous treatment, an alcohol 70% cleaning and application of silane. The groups ETA and ERA received adhesive application. For analysis in confocal laser microscope, were added to the primer adhesive system and the self-adhesive cement, the fluorescent dye rhodamine B isothiocyanate RITC 0.01%. Each root third passed for the push-out test, with a speed of 0.5 mm / min and to verify the penetration and adaptation of the cement in the root dentin analysis were made under confocal laser scanning microscopy. Subsequently each of the specimens were analyzed in scanning electron microscopy, the failures were classified (AD) adhesive; (MI) mixed and (CO) cohesive. For statistical analysis of the results, were selected two criteria: the tests two-way ANOVA and the Tukey test (α <0.05). As a result for push out bond strength ETA showed higher bond strength to radicular dentin than the other groups (p < 0.05) in all radicular thirds. Endodontic retreatment interfered negatively on the penetrability and on the push out bond strength of RelyX ARC and U200 cements to dentin, regardless of the analyzed radicular third.